2004
DOI: 10.1080/15287390490492467
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Growth, Secondary Sex Characteristics, and Reproduction of Fathead Minnows Exposed for a Life Cycle to Bleached Sulfite Mill Effluent

Abstract: To assess the potential effects of exposure to bleached sulfite mill effluent, long-term fathead minnow (Pimephales promelas) exposures were carried out on-site at the pulp mill secondary treatment lagoons. Exposure concentrations included 0, 1, 3, 10, 30, 50, or 100% final effluent, with the synthetic estrogen ethinylestradiol (10 ng/L) as a positive control compound. Fertilized minnow eggs were hatched in effluent and monitored through 140 d posthatch. The effluent produced a significant increase in the grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 16 publications
0
36
0
Order By: Relevance
“…and increased in male and decreased in female FHM exposed to 30% effluent. While several studies have shown a reduced performance of fish after exposure to PME (delayed maturation, reduced egg size, reduced egg production, and smaller gonads) [9,10,15,[34][35][36][37], the improved performance of fish has also been documented [9,12,36,38]. Testosterone depressions were observed in male and female mummichog exposed for 30 or 60 d to 50% CME following installation of a reverse-osmosis effluent treatment system [27,33] and in females at 1 and 50% concentrations [26].…”
Section: Discussionmentioning
confidence: 99%
“…and increased in male and decreased in female FHM exposed to 30% effluent. While several studies have shown a reduced performance of fish after exposure to PME (delayed maturation, reduced egg size, reduced egg production, and smaller gonads) [9,10,15,[34][35][36][37], the improved performance of fish has also been documented [9,12,36,38]. Testosterone depressions were observed in male and female mummichog exposed for 30 or 60 d to 50% CME following installation of a reverse-osmosis effluent treatment system [27,33] and in females at 1 and 50% concentrations [26].…”
Section: Discussionmentioning
confidence: 99%
“…Hewitt, Environment Canada, Burlington, ON, unpublished data) shows the presence of compounds with estrogenic activity in screenings of the final treated effluent from this mill. Development of ovipositors and feminization of mature male fish has been shown to be a sensitive indicator of estrogenic effects in FHM full life鈥恈ycle tests [28]. Development of ovipositors in mature male fish after exposure to bleached sulfite effluent also has been reported by Parrott and Wood [14], in which 18% of males exposed to 3.2% (v/v) effluent, 25% exposed to 10% (v/v) effluent, and 47% exposed to 32% (v/v) effluent developed ovipositors.…”
Section: Discussionmentioning
confidence: 99%
“…This estrogenic response differs from the results in the Northern Hemisphere. Worldwide, the principal response in sites downstream of pulp mill discharge has been a reduction in gonad size, as has been seen in Canada [7,[33][34][35][36][37][38][39], the United States [40][41][42], Sweden [43], Finland [44], and New Zealand [45], where the possible causes are a reduction in the fish's steroid production capacity [46][47][48]. The alterations we observed at the reproductive level in individuals downstream of the discharge could be responsible for the differences in the size structure of the populations of both species, in which there is a temporal tendency toward a loss of smaller sizes.…”
Section: Discussionmentioning
confidence: 99%